(untitled) (Journal of the College of Basic Education, 2026)
The current research aims to investigate the impact of the exit card strategy on the achievement of Arabic grammar among fifth-grade primary school students. In light of the research and its procedures, the null hypothesis was verified: There is no statistically significant difference at the significance level (0.05) between the average achievement scores of students in the experimental group and the average achievement scores of students in the control group. The researcher adopted a two-group experimental design, and the research sample consisted of (65) fifth-grade primary school students at Al-Taakhi Elementary School within the First Rusafa Education Directorate. The researcher rewarded the two research groups based on the students’ chronological age, calculated in months, parents’ academic achievement, and fourth-grade Arabic language scores. The researcher formulated (56) behavioral objectives distributed across the three lower levels of Bloom’s taxonomy. He also prepared an achievement test as a research tool consisting of (30) items distributed across the six grammar topics. The researcher used appropriate statistical methods in his research procedures. The research results showed that students in the experimental group outperformed students in the control group. The researcher recommended adopting the exit card strategy when teaching grammar at the elementary level and conducting studies on the exit card strategy in teaching Arabic language branches and other educational subjects.